Contribution of Independent Learning and Learning Motivation to Learning Outcomes of Islamic Religious Education Students of State Senior High School 1 Sei Rampah - Wijaya, Candra; Ananda, Rusydi; Baskoro, Agung (Budapest International Research and Critics University, 2021)
This study aims to determine: (1) the positive and significant contribution of learning independence to the learning outcomes of Islamic Religious Education, (2) the positive and significant contribution of learning motivation to the learning outcomes of Islamic Religious Education, and (3) the positive and significant contribution of learning independence and motivation. Study together on the learning outcomes of Islamic Religious Education? The research was conducted at SMA Negeri 1 Sei Rampah. This research is a quantitative research with correlation research method. The population in this study were all students of class XI which consisted of 8 classes totaling 240 students. The research sample amounted to 72 students who were taken by random sampling technique. The data collection instruments used were questionnaires and tests. Analysis of the data used is correlation and regression. The research findings show: (1) there is a positive and significant contribution between learning independence and learning outcomes with a correlation number of 0.354 with the regression line equation Å¶ = 71.60 + 0.23X1, (2) there is a positive and significant contribution between learning motivation and learning outcomes. With a correlation number of 0.473 with the regression line equation Å¶ = 68.96 + 0.28X2. and (3) there is a positive and significant contribution between learning independence and learning motivation with learning outcomes with a correlation number of 0.549 with the regression line equation Å¶ = 138.80 + 0.18X1 + 0.25X2. The effective contribution of the learning independence variable to learning outcomes is 9.90%, while the effective contribution of the learning motivation variable to learning outcomes is 20.00%.